Design and Analysis of Flexible Hinge Using in Optoelectronics Packaging Platform - Zheng Jiamain; 2Zhou Haibo; 2Huang Kai (Jixie chuandong)
In the six degrees of freedom flexible parallel platform using in optoelectronics packaging,the performance of the flexible hinge is an important influence factor on moving platform workspace and precision.According to Castigliano’s theorem and Lobatto quadrature formula,the mechanical model of the corner- filleted is established and the compliance matrix of flexible hinge is deduced. At the same time,the performance parameters of flexible hinge are defined,they are the rotation ability θ and rotation accuracy σ. On this basis,the impact of corner- filleted flexible hinge structural parameters L,d,r on its rotational capacity θ and rotational accuracy σ is calculated and analyzed,and it is verified by the finite element method. The results show that enhancing L and r,reducing d can improve the performance of flexible hinge. A strong basis for the flexible parallel motion platform design using in optoelectronics packaging is provided.